Pembuatan Barcode Kemasan Produk Pada CV. Kuliner Makmur Sejahtera Kota Padang - Maryam, Maryam; Alfi, Rizki; Senjawati, Maria Isfus; Putri, Gustiarini Rika; Arsil, Fikri; Syahmer, Verra; Nadiyah, Khairun (Journal of Industrial Community Empowerment, 2024)
Rendang, a traditional Minangkabau dish from West Sumatra, Indonesia, has gained international recognition and has inspired many entrepreneurs to promote this cuisine globally. One such entrepreneur is CV. Kuliner Makmur Sejahtera (KMS), which produces rendang under the brand Katuju. To enhance operational efficiency and support global market expansion, KMS requires an improved inventory management system. The primary challenge is the difficulty in monitoring inventory and tracking products without a barcode system. This community service program aims to address this issue by implementing barcode technology on Katuju's product packaging. The activities include designing, creating, and printing barcodes, as well as training KMS staff on how to use them. The process starts with observation and interviews to identify needs, followed by barcode design and production using an online barcode generator, and testing the barcode functionality with a scanning system. The results indicate that the community service team successfully trained KMS in barcode creation and printing, and integrated barcodes into product packaging. Evaluation through questionnaires showed participant satisfaction with the program and readiness to apply the barcode system to their products. This program is expected to improve inventory management, data accuracy, and support CV. KMS's global market expansion by providing tools necessary for efficient product tracking and valuable consumer data collection.